Pemanfaatan Sumber Daya Alam Pasir Laut sebagai Komoditas Tambang Masyarakat di Perairan Kabupaten Karimun, Kepulauan Riau - Muammar Gomareuzzaman (Syntax Corporation Indonesia, 2024)
Potential mining commodities in Karimun Regency, Riau Islands Province, include: tin, granite, land sand and sea sand. Areas in Karimun Regency that have the potential for sea sand are Babi Island Waters, Meral District, Karimun Regency and Tulang Village Waters, Selat Gelam District, Karimun Regency. This study was carried out to measure the optimal level of utilization of natural sea sand resources that can guarantee its sustainability. This is done by measuring the level of availability of sea sand; and measuring available sea sand reserves, the level of utilization that does not erode reserves, as well as estimated supply projections for future needs. The method used is the observation method, by collecting field data. Data were analyzed descriptively, with bathymetry measurements, spatial analysis using Geographic Information Systems (GIS), and literature study. The resources of the Community Mining Area with sea sand as a commodity in area A of Babi Island waters are 1,174,626.58 m3 and the resources of the Community Mining Area in area B of Gelam Strait waters are 502,088.58 m3